Die Geschichte Tirols im Spiegel der landesfürstlichen Residenz Schloss Tirol. Die Residenzen der Tiroler Landesfürst_innen bis um 1500 - Katharina Blasinger (Historia.scribere)
Tyrol Castle can be referred to as a ‘Dynastenburg’, as it was the ancestral seat of power for the Counts of Tyrol. Under the rule of Meinhard II (1259–1295) the castle developed to the centre of his power and came to be the place of residence for the princely family and their court. In the year 1420 the ancestral seat was relocated to Innsbruck and thus Tyrol Castle lost its representative power and function as a residence, falling into decay as a consequence. The combination of power and representation as well as its impact on buildings structures is crucial for this analysis.